Esophageal cancer and body mass index: results from a prospective study of 220,000 men in China and a meta-analysis of published studies. - Smith, M; Zhou, M; Whitlock, G; Yang, G; Offer, A; Hui, G; Peto, R; Huang, Z; Chen, Z (2008)
Several epidemiological studies have reported on the association between body mass index (BMI) and risk of esophageal cancer, but these were mostly in Western populations where many are overweight or obese. There is little direct evidence about the relationship in China where the mean BMI is relatively low and the disease rate is high. We examined the data from a population-based prospective study of 220,000 Chinese men aged 40-79 without a previous history of cancer (mean BMI 21.7 kg/m(2)), which included 1,082 esophageal cancer deaths during 10 years of follow-up. Adjusted hazard ratios for death from esophageal cancer by baseline BMI category were calculated using Cox proportional hazards models. Even among men with good self-assessed health and BMI >or= 18.5 kg/m(2), there was a strong inverse association between BMI and death from esophageal cancer, with each 5 kg/m(2) higher BMI associated with 25% (95%CI: 11-36%) lower esophageal cancer mortality. This inverse association persisted when analysis was restricted to men who had never smoked or when the first 5 years of follow-up were excluded. The strength of the relationship was consistent with the pooled estimate for squamous cell carcinoma of the esophagus in a meta-analysis of prospective studies (31% lower relative risk per 5 kg/m(2) higher BMI; 95% CI: 25-37%), but contrasted with that for adenocarcinoma which showed a positive association with BMI. Together, these data provide reliable evidence that in many populations low BMI is associated with an increased risk of squamous cell carcinoma of the esophagus.